Effect of Load on Tribological Characteristics of H-AlSi24Cu3.8Mg0.8 Alloy Under Dry, Lubricated, and Coated (a–c: H) Sliding Conditions - M. Peeru Naik; K. T. Balaram Padal; Muralidhar Avvari (Advances in Materials Science and Engineering)
This paper presents the new route of fabrication of H-AlSi24Cu3.8Mg0.8 alloy, assisted by ultrasonic vibration stirring and squeeze casting (UVSS). The primary objective of this investigation is to establish the tribological characteristics of the prepared aluminium alloy under dry, lubricated, and coated sliding conditions. Oil SAE20W40 is used as a lubricant and diamond-like carbon (DLC) is used as a coating. Under a load between 20 N and 50 N, a linear reciprocating tribometer (LRT) with a ball-on-plate geometry is used. Alloy was examined using an optical microscope, scanning electron microscope with EDS, 3D surface profilometer, Brinell hardness tester, and tensometer for pre- and postcharacterization of alloy, surface, and worn tracks. The DLC-coated condition yields the lowest wear and coefficient of friction.